2021
DOI: 10.1371/journal.pone.0245822
|View full text |Cite
|
Sign up to set email alerts
|

Sequence and structure comparison of ATP synthase F0 subunits 6 and 8 in notothenioid fish

Abstract: Mitochondrial changes such as tight coupling of the mitochondria have facilitated sustained oxygen and respiratory activity in haemoglobin-less icefish of the Channichthyidae family. We aimed to characterise features in the sequence and structure of the proteins directly involved in proton transport, which have potential physiological implications. ATP synthase subunit a (ATP6) and subunit 8 (ATP8) are proteins that function as part of the F0 component (proton pump) of the F0F1complex. Both proteins are encode… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 78 publications
0
4
0
Order By: Relevance
“…Proteins identified in the otoliths that are linked to mitochondrial processes included ADP/ATP translocase, which belongs to the mitochondrial carrier family [49]. We also found the ATP-binding cassette sub-family B (MDR/TAP), which regulates apoptotic and non-apoptotic cell death [50]; the ATP synthase-coupling factor 6, which was reported to be essential for energy transduction [51]; and the ATP synthase subunits alpha and beta that generate electron transport complexes for the respiratory chain [52]. Finally, we identified the voltage-dependent anion-selective channel 2 (VDAC2) protein, which is known to contribute to oxidative metabolism by facilitating solute transport across the outer mitochondrial membrane (OMM).…”
Section: Mitochondrial Processesmentioning
confidence: 86%
“…Proteins identified in the otoliths that are linked to mitochondrial processes included ADP/ATP translocase, which belongs to the mitochondrial carrier family [49]. We also found the ATP-binding cassette sub-family B (MDR/TAP), which regulates apoptotic and non-apoptotic cell death [50]; the ATP synthase-coupling factor 6, which was reported to be essential for energy transduction [51]; and the ATP synthase subunits alpha and beta that generate electron transport complexes for the respiratory chain [52]. Finally, we identified the voltage-dependent anion-selective channel 2 (VDAC2) protein, which is known to contribute to oxidative metabolism by facilitating solute transport across the outer mitochondrial membrane (OMM).…”
Section: Mitochondrial Processesmentioning
confidence: 86%
“…Several studies have revealed the biochemical consequences of amino acid replacement of mtATP6 and indicated that they may alter mitochondrial ATP production, ranging from 30 to > 90% [ 51 54 ]. In another study, the mtATP6 of Champsocephalus gunnari (ice fish) was compared with the same protein from a few vertebrate species, and their data revealed that the variations observed between them could affect the structure and function of the protein leading to the unique physiology of the ice fish [ 55 ]. A similar effect might occur due to the variations observed at 6 positions in mtATP6 of P. muticus .…”
Section: Discussionmentioning
confidence: 99%
“…Icefish have been previously reported to show an increased coupling of proton transport and ATP synthase compared with red-blooded notothenioids [ 51 ] and this could be correlated to the increase in the specific subunits of complex V that are directly involved in proton translocation. Previously, we have shown the ATP synthase subunit 6 of complex V to be sequentially and structurally different in the icefish C. gunnari when compared to its red-blooded related species [ 52 ].…”
Section: Discussionmentioning
confidence: 99%